Serve speed and its influence on performance effectiveness in junior sitting volleyball: Evidence from the V Parapan American Youth Games 2023 - Martin, W. F.; Rodriguez Aponte, J. F.; Pardo, Y. R.; Cardozo, L. A.; Gomez Solano, J. H.; Tellez, L. A.; Peña Ibagon, J. C. (Journal of Physical Education and Sport, 2025)
Background: The serve in sitting volleyball is a fundamental skill that contributes to both offensive and defensive team strategies, serving as the initial opportunity to exert control over the rally. Its effectiveness can influence the opponent`s reception, limit attacking options, and create scoring opportunities. Despite its importance, there is limited scientific evidence regarding the determinants of an effective serve, particularly within junior elite categories of para-volleyball, where technical and tactical demands differ from the standing version of the sport. Objective: To examine the relationship between serve speed and performance effectiveness in elite junior sitting volleyball players. Methods: A total of 593 serves were recorded during the V Parapan American Youth Games 2023. Ball velocity was measured using a Stalker Sport 2 radar gun. Serve effectiveness was evaluated through systematic observation, in which four trained experts categorized each serve into four predefined performance levels. Statistical analyses compared ball speed according to serve type and sex and assessed associations between velocity and effectiveness. Results: Significant differences in ball velocity were found between serve types (p < 0.05), with jump serves presenting higher speeds than standing serves. No significant differences in serve speed were observed between male and female athletes. Furthermore, there was no statistically significant association between serve speed and performance effectiveness (p > 0.05). Conclusions: In elite junior sitting volleyball, faster serves do not necessarily result in higher effectiveness during competition. These findings challenge the assumption that increased ball speed automatically enhances performance outcomes, highlighting the need to integrate tactical precision, placement strategies, and technical consistency alongside speed development in training programs for paravolleyball.